2012
DOI: 10.1590/s1677-04202012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic analyses of two native Atlantic Forest species in regenerative understory of eucalyptus plantation

Abstract: Gas exchange, chlorophyll a fluorescence, and photosynthetic pigments of Xylopia sericea A. St.-Hil. and Siparuna guianensis Aubl. were evaluated during the rainy season and the dry season (2009)(2010) in three understories with different ecological conditions (irradiance, water availability, and temperature) located in the União Biological Reserve (known as REBIO União), at Rio de Janeiro State, a natural forest understory, eucalyptus understory under regeneration, and understory of eucalyptus plantation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
2
10
0
2
Order By: Relevance
“…The data show that the main species regenerating in the understory can increase carbon gain and tolerate more irradiance after management. These data in addition to previous studies (Evaristo et al, 2011;Lage-Pinto et al, 2012;Lage-Pinto et al, 2015;Silva et al, 2010;Teixeira et al, 2015;Vieira et al, 2015) show the photoacclimation performance of these species to more irradiance, that could explain their abundance in the open and management areas. Thus, there is a possibility that the management may affect the trajectory of forest regeneration, including potential dominance of these species.…”
Section: Forest Regeneration and Physiological Characteristics Of Thesupporting
confidence: 79%
See 2 more Smart Citations
“…The data show that the main species regenerating in the understory can increase carbon gain and tolerate more irradiance after management. These data in addition to previous studies (Evaristo et al, 2011;Lage-Pinto et al, 2012;Lage-Pinto et al, 2015;Silva et al, 2010;Teixeira et al, 2015;Vieira et al, 2015) show the photoacclimation performance of these species to more irradiance, that could explain their abundance in the open and management areas. Thus, there is a possibility that the management may affect the trajectory of forest regeneration, including potential dominance of these species.…”
Section: Forest Regeneration and Physiological Characteristics Of Thesupporting
confidence: 79%
“…This suggests that photodamage is reversible in young leaves. Although these species show photoacclimation capacity (Silva et al, 2010;Lage-Pinto et al, 2012;Teixeira et al, 2015;Vieira et al, 2015), dynamic photoinhibition had been observed 1 year after management for S. guianensis and X. sericea in this area (Lage-Pinto et al, 2012). All species are able to photoacclimate,, but B. sericea is the fastest species to recuperate initial conditions after forest management (Teixeira et al, 2015).…”
Section: Influence Of Forest Management On Photosynthetic Performancementioning
confidence: 86%
See 1 more Smart Citation
“…This result suggests that the plants showed very little reduction towards the critical limit, suggesting that they have some evolutionary characteristic to tolerate water shortage. According to the literature, F V /F M decreases under conditions of low water availability, leading to an increase in the photoinhibition processes (Lage-Pinto et al 2012).…”
Section: An Acad Bras Cienc (2017) 89 (4) Water Availability In the Mmentioning
confidence: 98%
“…e Siparuna guianensis Aubl. sob três condições luminosas naturais: [1) sub-bosque de floresta natural, 2) sub-bosque de eucalipto sob regeneração e 3) sub-bosque de plantação de eucalipto com árvores de 18 anos que foram removidas um ano antes foi avaliada sob estações de seca e chuva(LAGE-PINTO et al, 2012). Esses autores observaram que, embora ambas espécies pertencem aos estágios iniciais de sucessão ecológica, apresentaram fotoinibição dinâmica após 1 ano de exposição a pleno sol em ambas as estações, acentuadamente na estação seca.…”
unclassified